Designing a Dashboard Together: Reporting the Experience of Co-creating a Customizable Dashboard System in a Workshop - Santana, Amanda; Sampaio, Lívia; Morais, Luiz Augusto; Brito, Andrey (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Visualization dashboards are considered ubiquitous, being widely used across many application contexts among very different user profiles. Due to this diverse nature, the process of designing dashboards becomes even more challenging, particularly, to meet requirements that are more sophisticated and varying as the more popular such dashboards become. In order to make the process of design dashboard more effective it is possible to find in the literature a number of results on methodologies, standards, or guidelines devoted to this end. This work contributes to the state of the practice by presenting an experience report on the use of workshops to streamline the dashboard design process. Workshops have been used in the context of data visualization systems as an alternative to the requirements gathering phase, providing faster and more economical means for extracting requirements from experts. Unlike other workshop applications that focus on the requirements gathering stage, we concentrate on the design conception stage where system design is conceived and structured. We employed the Dashboard Design Patterns Workshop methodology by Bach et al. to conduct a workshop with the development team of a real dashboard for intelligent and tailored resource management (energy, water, etc.). Following the workshop, data was collected from its participants (via surveys and interviews) at two temporal points: on the day of the workshop itself and several months later when the focused dashboard was completed. Based on these data, we highlight the improved collaboration among team members, better understanding of the system as a whole, and increased autonomy. On the other hand, shortcomings such as the limited time dedicated to executing the workshop itself were identified, leading to uncertainties in some stages and consequently, in the results regarding the dashboards generated during the workshop. This article unfolds the narrative of our journey, demonstrating the transformative impact of workshops on guiding visualization design.